Predicting 4-Year Graduation: Using Social Cognitive Career Theory to Model the Impact of Prescriptive Advising, Unit Load, and Students' Self-Efficacy. (February 2021) - Bolkan, San; Pedersen, William C.; Stormes, Kaitlyn N.; Manke, Beth
In this study, we investigated how environmental, cognitive, and demographic variables influenced students' ability to graduate from a 4-year university in 4 years. Specifically, we examined how behaviors related to social cognitive career theory (i.e., self-efficacy, outcome expectations, and academic goals) were influenced by contextual experiences related to prescriptive academic advising to ultimately predict students' ability to graduate in 4 years. After holding students' demographic characteristics constant, results from structural regression analyses indicated that prescriptive advising had a direct effect on students' 4-year graduation rates. In addition, prescriptive advising had indirect effects on students' 4-year graduation rates through its impact on students' self-efficacy and the serial path involving students' self-efficacy and their academic goals. Our results suggest that if institutions want to ensure they maximize 4-year graduation rates, helping students understand that it is possible to graduate in 4 years is critical.